Prevalence and Patterns of Omeprazole and H2 Blocker Use in Neonates in a Neonatal Intensive Care Unit Setting: Omeprazole and H2 Blockers in Neonates - Iqbal, Shahid; Javed, Irum; Quddus, Muhammad Abdul; Munawar, Rukhsana (Pakistan Journal of Health Sciences, 2024)
H2 blockers and omeprazole therapy have not been shown to improve clinical symptoms associated with stress ulceration in newborn trials. There were concerns regarding the reliability and efficacy of treating stress ulcers in adults and children with omeprazole and H2 blockers. Objective: To investigate the prevalence and patterns of H2 blocker and omeprazole use in neonates, assess their efficacy, and evaluate potential risks associated with their use. Methods: Sick infants admitted to NICUs within the Department of Pediatrics ‘Sheikh Khalifa Bin Zaid Al Nahyan Hospital’, Rawalakot, Azad Kashmir were included in this retrospective study. Data collection was done from the hospital records from January 2022 to December 2022. All NICU infants who were at least 28 days old, were critically sick participated in this investigation. Results: There was a twice as high frequency of omeprazole use as of H2 blocker use. More frequently used drugs were Omeprazole and Cimetidine. That was from January to December in the year 2023 Omeprazole group rose from 3. 1% to 3. 8% and the H2 blocker group rose from 1. 3% to 1. 9%. Conclusions: Hospitalized neonates including those without GIT issues were commonly exposed to prescriptions of H2 blockers end Omeprazole. The findings depicted the need for controlling and effectively utilizing omeprazole and H2 blockers. Hence there was a need for more research in relation to the safety and efficacy of omeprazole and H2 blockers in infants.